Improving Patient Safety During the COVID-19 Pandemic: Literature Review - Deasy Amelia Nurdin (Yayasan Pendidikan Medika Indonesia, 2021)
The COVID-19 pandemic has had a profound impact on the health care system. Hospitals are required to be able to quickly change the design of their services, including in terms of resources and technology, which will become a new risk for patient safety. The lack of number of health workers and the increasing workload cause fatigue which has the potential to injure patients. Reports from the Pennsylvania Patient Safety Reporting System (PA-PSRS) from January 1, 2020 to April 15, 2020, there were 343 incident reports originating from 71 hospitals. This literature review aims to find out an overview of patient safety during the COVID-19 pandemic and the steps that can be taken to improve it. Reference searches were conducted electronically sourced from PubMed, ISQua, and Google Scholar. From the results of the analysis, it was found that patient safety must always be a priority in hospital services even during the COVID pandemic. Strategies that can be taken to improve patient safety during the COVID-19 pandemic are strengthening organizational systems, supporting patients and empowering the community, increasing safety in care, minimizing the risk of injury, and improving the learning system.